Insights into Vortex Shedding with Data Analysis - Jiun-Jih MIAU; J. K. TU; T. W. LIAO (Journal of Fluid Science and Technology, 2009)
Unsteady, three-dimensional characteristics of vortex shedding were studied with self-made MEMS sensors situated spanwisely on a circular cylinder subjected to uniform incoming flow. Firstly, verification on the reliability of the MEMS sensor signals was made by comparing with the hot-wire signals obtained in the flow simultaneously. Subsequently, the MEMS sensor signals were analyzed with Wavelet and Hilbert transformations and 2D-FFT. By Wavelet and Hilbert transformations, the results obtained indicate that the strongly three-dimensional vortex shedding events are featured with pronounced spanwise variations in the instantaneous phases of vortex shedding, which are further identified as the occurrences of vortex dislocation. Furthermore, the results of 2D-FFT analysis reveal that the spanwise wave numbers of vortex shedding largely falls in a range between -2 to 2, for the MEMS sensors spanned over a spanwise region of 3 D in length.